Non-communicable diseases: Opportunities to promote future health during the first 1000 day of life - Macnab, Andrew John (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
The Developmental Origins of Health and Disease (DOHaD) framework now underlies the evolution and epigenetics of many non-communicable diseases that develop in adult life. Type 2 diabetes, obesity, hypertension, heart disease and stroke in particular have links back to events during the first 1000 days of life, and as the world is witnessing an epidemic of these conditions, identifying measures able to contribute to reducing the potential for these NCDs to develop in our aging populations becomes all the more important. Parental health at conception and good maternal health and nutrition throughout pregnancy are known to be integral to normal infant development and health in later life, but more recently the central importance of infant nutrition that achieves healthy weight gain has become recognized. In this context, achieving growth patterns for infants that avoid either the onset of obesity or development of stunting during the first 1000 days of life appears to be an achievable goal with significant potential for the avoidance of many NCDs in later life. Hence the relevance of health promotion initiatives to share this knowledge among health care providers and educate parents on the benefits of optimal infant nutrition.